Effectiveness of Lecture Cum Demonstration on First Aid Management of Common Ailments in Terms of Knowledge among Accredited Social Health Activist (Asha) Workers - Asha Nadar; Uma. J.Deaver; Sunil Kumar Dular; Rekha Chhillar (Indian Journal of Forensic Medicine & Toxicology, 2021)
Death can occur at any time in which first aid is the initial step of giving care to a person in the emergency. Everyone has the capability to save lives during the emergency situation to reduce the further complications. The present study aimed to assess the effectiveness of lecture cum demonstration on first aid management of common ailments in terms of knowledge and practice among accredited social health activist (ASHA) workers. Study was Quasi experimental one group pre-test post-test design. Total 52 ASHA workers were selected by using Total enumeration sampling technique. Data was collected by using structured knowledge questionnaire and observational checklist through paper pencil technique. The mean post-test knowledge score (25.21±2.77) was higher than the mean pre-test knowledge score (11.25±4.24) and mean post-test practice score(64.54± 3.10) was higher than the mean pre-test practice score (9.71± 3.42). There was no significant association of post-test knowledge score with selected variables except marital status and there was no significant association of mean post-test practice score with selected variables. The study concludes that lecture cum demonstration was effective in improving the knowledge and practice of ASHA workers on first aid management of common ailments.